Asbabun nuzulAyat Al-Qur’an Berkaitan Produktivitas dan Media Pembelajaran Online - Meinarini Catur Utami; Suci Ratnawati (Universitas Darussalam Gontor, 2022)
Humans were created by Allah SWT has one purpose, worship to Allah, not associate with Allah, and not commit immorality. Therefore, we need a source of guidance in carrying out our daily activities, namely the Al-Qur’an and Al-Sunnah. Learning activities are one of human’s daily activities that are crucial according to religion because by gaining knowledge through the learning process, it will be able to lead a human life in a better direction and to know right and wrong. During this pandemic, learning activities changed drastically, from offline to online. This change makes the writer interested in reviewing the verses of the Qur’an to examine it in terms of learning media and productivity when doing online activities. The author conducts a search for asbabun nuzulverses and an explanation of verses related to this, to ensure that the implementation of Distance Learning is correct according to the Qur’an so that learning benefits are maintained.